Protective effect of calcitonin on lumbar fusion-induced adjacent-segment disc degeneration in ovariectomized rat. Issue 1 (December 2015) - Liu, Chang-Cheng; Tian, Fa-Ming; Zhou, Zhuang; Wang, Peng; Gou, Yu; Zhang, Heng; Wang, Wen-Ya; Shen, Yong; Zhang, Ying-Ze; Zhang, Liu
Abstract Background Intervertebral disc (IVD) degeneration and pathological changes in the spinal cord are major causes of back pain. In addition to its well-established anti-resorptive effect on bone, calcitonin (CT) potentially exerts protective effects on IVD degeneration in ovariectomized rats. However, possible therapeutic effects of CT on lumbar fusion-induced adjacent-segment disc degeneration (ASDD) have not been investigated yet. In this study, we examined the effects of CT on IVD degeneration adjacent to a lumbar fusion in ovariectomized rats. Methods Posterolateral lumbar fusion (PLF) at L4–5 was performed 4 weeks after ovariectomy (OVX) or sham surgery in female Sprague–Dawley rats. Following PLF + OVX, rats received either salmon CT (OVX + PLF + sCT, 16 IU/Kg/2d) or vehicle (OVX + PLF + V) treatment for 12 weeks; the remaining rats were divided into Sham + V, OVX + V, and PLF + V groups. Fusion status was analyzed by manual palpation and radiography. Adjacent segment disc was assessed by histological, histomorphometric, immunohistochemical analysis. L6 vertebrae microstructures were evaluated by micro-computed tomography. Results Histological analysis showed more severe ASDD occurred in OVX + PLF + V rats compared with the OVX + V or PLF + V groups. CT treatment suppressed the score for ASDD, increased disc height, and decreased the area of endplate calcification. Immunohistochemical staining demonstrated that CT decreased the expression of collagen type-I, matrix metalloproteinase-13, and a disintegrin and metalloproteinase with thrombospondin motifs-4, whereas it increased the expression of collagen type-II and aggrecan in the disc. Micro-computed tomography indicated that CT increased bone mass and improved the microstructure of the L6 vertebrae. Conclusions These results suggest that CT can prevent ASDD, induce beneficial changes in IVD metabolism, and inhibit deterioration of the trabecular microarchitecture of vertebrae in osteoporotic rats with lumbar fusion.